Pelatihan Tes Potensi Skolastik (TPS) dan Tes Penalaran Matematika Bagi Siswa SMKS Yusuf Abdussatar Kediri - Karina Nurwijayanti; Henni Comala Hikmi; Emi Suryadi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
Most vocational high school (SMK) students lack adequate information regarding Scholastic Aptitude Tests (TPS) and Mathematical Reasoning Tests, which are critical components of university entrance examinations. This issue was observed among students at SMKS Yusuf Abdussatar Kediri, who demonstrated limited understanding of both test domains. This community service initiative aimed to enhance students' comprehension, skills, and preparedness in facing the TPS and Mathematical Reasoning Tests. The program was implemented through a four-stage framework: observation, preparation, execution, and evaluation. The intervention was delivered in person, targeting students of SMKS Yusuf Abdussatar Kediri as the primary participants. The program activities included instructional sessions on test material, provisioning of sample problems, strategy training for problem-solving, group discussions, and evaluation via a pretest and posttest design. Evaluation results indicated an improvement in students' abilities to solve scholastic aptitude and mathematical reasoning problems compared to their baseline scores, although the increase was not highly significant. Consequently, this training program serves as a strategic effort to foster student readiness, skills, and conceptual understanding for higher education entrance exams.